Heterotrophy of Oceanic Particulate Organic Matter Elevates Net Ecosystem Calcification - Andrea K. Kealoha; Kathryn E.F. Shamberger; Emma C. Reid; Kristen A. Davis; Steven J. Lentz; Russell E. Brainard; Thomas A. Oliver; Michael S. Rappé; E. Brendan Roark; Yoshimi M. Rii (Geophysical Research Letters)
Abstract Coral reef calcification is expected to decline due to climate change stressors such as ocean acidification and warming. Projections of future coral reef health are based on our understanding of the environmental drivers that affect calcification and dissolution. One such driver that may impact coral reef health is heterotrophy of oceanic‐sourced particulate organic matter, but its link to calcification has not been directly investigated in the field. In this study, we estimated net ecosystem calcification and oceanic particulate organic carbon (POCoc) uptake across the Kāne'ohe Bay barrier reef in Hawai'i. We show that higher rates of POCoc uptake correspond to greater net ecosystem calcification rates, even under low aragonite saturation states (Ωar). Hence, reductions in offshore productivity may negatively impact coral reefs by decreasing the food supply required to sustain calcification. Alternatively, coral reefs that receive ample inputs of POCoc may maintain higher calcification rates, despite a global decline in Ωar.